Enhancing Critical Thinking in Chemistry Education Through Differentiated LKPD Design - Wahyuni, Sri; Hasan, Muhammad; Saminan, Saminan (Heca Sentra Analitika, 2025)
This research aims to enhance students' Critical Thinking Skills in chemistry learning by using differentiated LKPD. Based on the initial observation, it was found that the CTS of students was still in the low category, as the learning media used had not taken into account the learning styles of students. This type of research is quasi-experimental with a Control Group Pre-Test-Post-Test Design. The sample in this study consisted of students from X.E-8, the experimental class, who were treated with differentiated LKPD, and the control class X.E-6, which was treated with undifferentiated LKPD. The research sample consisted of 76 students. The data collection employed a description test, consisting of five questions. Normality, homogeneity, and the One-Way ANOVA test were employed to analyze the data. The results of the feasibility test of differentiated LKPD, in terms of presentation, content, language, and writing, obtained an Aiken index of 0.87 and an Inter-Rater Agreement of 0.617, indicating that LKPD is valid and reliable. So, it is feasible to use as a chemistry learning medium. Based on the one-way ANOVA test analysis, it was found that there was a significant difference in the improvement of critical thinking skills between students taught using differentiated LKPD in the experimental class and those taught using undifferentiated LKPD in the control class.